Penyuluhan kepada Masyarakat Pelosok Kabupaten Karawang tentang Pentingnya Membayar Pajak Kendaraan Bermotor - Anita, Widya Febryari; Muhammad, Rabhi Fathan; Wardhani, Rulyanti Susi (Jurnal ETAM, 2024)
Motor Vehicle Tax is one of the Local Taxes whose revenue is highly relied upon in the Local Own-Source Revenue of West Java Province. The revenue from this type of tax has the potential to be optimized, especially in Karawang Regency, which is in line with the fact that there are still many remote communities in this area that still need motorized vehicle registration numbers or have expired. For this reason, counseling activities are needed for remote communities in Karawang Regency to increase awareness and compliance with paying motor vehicle tax obligations. The method of community service uses the counseling method. The results of the counseling activities provide various benefits for the government and the people of Kalidungjaya Village, the Subregional Police of Karawang, and the Regional Revenue Management Center of Karawang Regency.